A numerical study of chemical reaction in a nanofluid flow due to rotating disk in the presence of magnetic field - Muhammad Ramzan (Nature Portfolio, 2021)
Abstract In this paper, a numerical study of MHD steady flow due to a rotating disk with mixed convection, Darcy Forchheimer’s porous media, thermal radiation, and heat generation/absorption effects are explored. A strong magnetic field is applied in perpendicular direction to the flow which governs the Hall current effects. Homogeneous and heterogeneous reactions are also taken into account. For the simplification of partial differential equations (PDEs) into the nonlinear ordinary differential equations (ODEs), the method of generalized Von Karman similarity transformations is employed, and the resulting non-dimensional ordinary differential equations are solved by using the homotopy analysis method (HAM). Effects of different parameters on the axial, radial and tangential velocity profiles, temperature and concentration of chemical reaction profiles are analyzed and discussed. The present work’s remarkable finding is that with the expansion of nanoparticles size, dimensionless constant parameter, local Grashof number, porosity parameter, Hall current, and suction parameter, the nanofluid radial velocity is enhanced. For the higher values of magnetic field parameter, the tangential velocity and nanofluid temperature are enhanced. The magnetic field parameter and the disk thickness coefficient parameter have similar impacts on the axial velocity profile. Heterogeneous chemical reaction parameter decreases the concentration of chemical reaction profile. The nanoparticles volume fraction increases the concentration of chemical reaction profile. Furthermore, the present results are found to be in excellent agreement with previously published work in tabulated form.